Ecological factors associated with behavioral problems in vulnerable children. Issue 3 (21st October 2016) - Choo, Jina; Kim, Hye‐Jin; Turk, Melanie T.; Kim, Eun‐Kyung; Yang, Kyung‐Sook
Abstract : Aim: Based on McLeroy's ecological perspective, this study aimed to identify the factors that are associated with behavioral problems among children who were enrolled in community child centers that provide public welfare services for vulnerable children. Methods: A cross‐sectional survey was conducted among 175 children aged 6–12 years and their parents who were recruited from 16 community child centers in a municipal county of Seoul, South Korea. The children's behavioral problems were reported by their parents and measured by the Child Behavior Checklist/6–18. As predictor variables, 14 potential factors were selected at multiple ecological levels; parents' health‐related quality of life was measured by the World Health Organization Quality of Life‐BREF. A multiple linear regression analysis was carried out. Results: At the intrapersonal level, children's chronic illness was significantly associated with internalizing problems. At the interpersonal level, lower parental health‐related quality of life was significantly associated with internalizing and externalizing problems. At the organizational level, more years since the community child centers were founded was significantly associated with social problems. At the community level, a lower population density in the district in which the community child center was located was significantly associated with internalizing problems. Conclusion: Among vulnerable children, behavioral problems were significantly associated with a comprehensive array of intrapersonal‐, interpersonal‐, organizational‐, and community‐level factors. These ecological factors that have been identified in the present study need to be considered when developing multilevel, community‐based nursing strategies for preventing and managing vulnerable children's behavioral problems.